Value Creation in Mergers, Acquisitions, and Alliances - Bösecke, Kathrin (Gabler Verlag : Imprint: Gabler Verlag, 2009)
Despite their increasing importance as strategic options for corporate growth mergers, acquisitions, and alliances often fail. Kathrin Bösecke analyses the factors that determine the success, i.e., value creation for shareholders, of business combinations. Her analysis of 126 acquisitions and 66 alliances in the European utility industry provides new and interesting results. For example, the origin of the participating firms as well as the target country of the business combination can be considered as essential determinants of value creation. Furthermore, acquisitions and alliances are better suited to some markets and regions than others.